THE EFFECT OF ADJUVANT OMEGA-3 THERAPY ON THE IMPROVEMENT OF CLINICAL SYMPTOMS AND TUMOR NECROSIS FACTOR ALPHA (TNF-ALPHA) SERUM LEVELS IN SCHIZOPHRENIC PATIENTS TREATED WITH RISPERIDONE - Syamsuddin Saidah; Abbas Nur Insani; Limoa Erlyn; Tawali Suryani; Hawaidah; Yustisia Ika; Lisal Sonny Teddy (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Objectives: The pathogenesis of schizophrenia remains unclear; However, neuroinflammation is considered a potential factor. Some researchers have also proposed that immune disorders may be involved in the etiology and pathophysiology of schizophrenia. Abnormal levels of cytokines and proinflammatory receptors have been found in peripheral blood and cerebrospinal fluid in schizophrenic patients. In recent years, growing attention has concentrated on the role of nutritional interventions in neurological and mental diseases to maximize the effects of nutritional components on brain function, neural plasticity, and mental health includingadministration of adjuvant therapy to help schizophrenic patients inachieve better life functions. This research conducted to determine the effectiveness of omega-3 to improve clinical symptoms and levels of TNF-αserum in schizophrenic patients.Method:This research is an experimental analysis, with a pre-posttest with control group approach (pretest-posttest randomized design), which was conducted at the Dadi Regional Special Hospital in South Sulawesi Province, Indonesia in January-April 2023 and sample testing was carried out at the UNHAS RSPTN Research Laboratory .The subjects of the study were 44 inpatient schizophrenia patients who received a therapeutic dose of risperidone and were randomly allocated to the treatment group and control group with a total of 22 people each. The treatment group was given Omega-3 capsules at a dose of 2400 mg (1 capsule)/24 hours/orally for 8 weeks. Improvement in clinical symptoms was measured using the PANSS (Positive and Negative Syndrome Scale) at week 0 (baseline), week 4, and week 8. Serum TNF-alpha markers of inflammation were measured at week 0 (baseline) and week 8 using the ELISA method.Conclusion: Administration of adjuvant omega-3 therapy contributed to better clinical symptom improvement in the first 4 weeks of therapy and reduced markers of TNF-alpha inflammation compared to the group that only received conventional antipsychotic therapy.